Abundance and diversity of soil mites (Acari) along a gradient of land use types in Taita Taveta, Kenya - Maribie, CW; Nyamasyo, GHN; Ndegwa. PN; Mung'atu, Joseph K.; Lagerlof, J; Gikungu, M (2011)
The abundance and diversity of soil mites was monitored along a gradient of land use types (LUTs) during the wet seasons in soils of Taita Taveta, Kenya. Sampling of mites from soils was carried out in eight LUTs which included maize-based system (Zea mays), coffee (Coffea Arabica), horticulture, napier grass (Pennisetum purpureum), fallow, pine (Pinus patula), cypress (Cypressus lusitanica), natural forest. LUT significantly influenced abundance, richness and diversity of the soil mites. During the short rains the diversity of soil mites increased in the order napier < maize-based system < horticulture < coffee < fallow < natural forest < pine forest < cypress plantation while the long rains season abundance increased in the order maize-based system < coffee < horticulture < napier < natural forest < fallow < pine forest < cypress forest. Higher abundance, richness and diversity of the mites was observed in the less disturbed forest ecosystems unlike the agro-ecosystems, which are often disturbed with intensive cultivation A total of 37 families were recorded with 20 oribatid families, 10 mesostigmatid families and 7 prostigmatid families. The families that ranked highest in abundance across the LUT were Scheloribatidae, Oppidae (Oribatida) and Rhodacaridae (Mesostigmata). LUT influenced significantly (P